Reading ‘House of Jacob’ in Isaiah 48:1-11 in light of Benjamin - Quine, Cat (Society of Biblical Literature, 2017)
Isaiah 48:1-11 has been described as a difficult passage due to a perceived discord between its harsh tone and the message of comfort espoused elsewhere in Isaiah 40-55. This paper analyses this passage with regard to four groups of arguments, namely, proposals of a Judahite origin for the text, the archaeological evidence for settlement continuity in the Benjaminite region in the Neo-Babylonian period, the development and use of the patriarchal traditions in the sixth century, and studies of hidden polemic. By drawing these together, this paper proposes that the house of Jacob in Isaiah 48:1-2, could be understood as addressing a sixth century Judahite community in the Benjaminite region, perhaps in the vicinity of Bethel.